Experience of Tsimitsifuti extract (Klimadinone®) use in the framework of complex rehabilitation of patients with cervical carcinoma - T. N. Kolomoytseva; O. A. Orlov; G. A. Kozlova (ABV-press, 2014)
Experience of Tsimitsifuti extract (Klimadinone®) use in the frameworkof complex rehabilitation of patients with cervical carcinoma